Antimicrobial effects produced by gold nanoparticles obtained with extracts of Allium sativum and Allium ursinum - Ioana Andreea BARBU; Rahela CARPA; Oana Maria BIRO; Marcel PÂRVU (Studia Universitatis Babeș-Bolyai. Biologia, 2025)
Gold nanoparticles (AuNPs) obtained by green synthesis using plant extracts from the genus Allium have attracted significant scientific interest due to their potential applications as antimicrobial agents in the biomedical field. This study investigates the antimicrobial potential of AuNPs obtained by green synthesis using extracts of Allium sativum and Allium ursinum. These plant extracts are rich in sulfur compounds (allicin), flavonoids and polyphenols, which not only facilitate the formation of nanoparticles, but also confer them increased antimicrobial properties. The nanoparticles thus obtained were characterized by spectroscopic methods (UV-Vis) and were tested for antimicrobial activity. Microbiological tests performed in vitro demonstrated an antimicrobial activity of the nanoparticles against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria but also against Candida albicans and Candida parapsilosis. The results support the idea that gold nanoparticles functionalized with Allium extracts may constitute a promising alternative in the development of natural antimicrobial compounds with applications in medicine, the food industry and the pharmaceutical field.